2008
DOI: 10.1039/b808344d
|View full text |Cite
|
Sign up to set email alerts
|

High conductivity and chemical stability of BaCe1−x−yZrxYyO3−δ proton conductors prepared by a sol–gel method

Abstract: High-temperature proton conductors are promising as electrolytes for intermediate-temperature solid oxide fuel cells. Among them, BaCeO 3 -based materials have high proton conductivity but rather poor chemical stability. In contrast, barium zirconates are rather stable, but have poorly reproducible densities and conductivities. In this study, the investigation of BaCe 1ÀxÀy Zr x Y y O 3Àd solid solutions (x ¼ 0, 0.10, 0.20, 0.30, 0.40; y ¼ 0.15, 0.20) was undertaken, with the final aim of finding a composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 32 publications
7
75
0
Order By: Relevance
“…BSCZGY and BZ3C5YYb for comparison were heated up to 1200 ºC in pure CO2 with a flow rate of 40 ml/min, held isothermally for 30 minutes and then cooled down with the same rate of 3 o C/min. The heat treatment in CO2 up 1200 º C or a bit higher has already been reported by many in the literature [14,35,40,49,50]. Fig.…”
Section: Chemical Stabilitysupporting
confidence: 52%
See 1 more Smart Citation
“…BSCZGY and BZ3C5YYb for comparison were heated up to 1200 ºC in pure CO2 with a flow rate of 40 ml/min, held isothermally for 30 minutes and then cooled down with the same rate of 3 o C/min. The heat treatment in CO2 up 1200 º C or a bit higher has already been reported by many in the literature [14,35,40,49,50]. Fig.…”
Section: Chemical Stabilitysupporting
confidence: 52%
“…For a composition with same Zr ratio i.e. 20 mol%, BaCe0.65Zr0.20Y0.15O3 -δ, a densification of 93% was achieved after firing at 1400 ºC for 10 hours [40]. The same material i.e.…”
Section: Microstructurementioning
confidence: 98%
“…These oxides show pure protonic conduction in wet hydrogen atmosphere, while they exhibit protonic, oxygen ionic and electronic mixed conduction under high oxygen partial pressure at elevated temperatures [6]. Major problem in case the of BaCe 1-xy Zr x YyO 3-d materials is the poor sinterability and they require very high temperature (i.e., above 1,700°C) for well sintering with pore free microstructure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Among various methods recently proposed to synthesize nano-crystalline powders, the modified Pechini method has the advantage to produce high purity and ultrafine powders. In previous investigations [6,18,19] we found that yttrium doped barium cerates (BaCe 1-y Y y O 3 with y = 0.1, 0.15, and 0.2) prepared by means of sol-gel route employing a barium excess gave high active nano-sized powders and sub-micrometric solid solutions. Sintering temperatures of 1,250°C for BaCeYO 3-d resulted in high densities.…”
Section: Introductionmentioning
confidence: 93%
“…The average particle sizes were about 0.1-0.3 micron. The preparation of specimens was similar to that in previous studies [6,18]. The resulting materials were characterized by various techniques.…”
Section: Specimens Preparationmentioning
confidence: 99%